Small amplitude oscillations before the L-H transition in EAST. (5th February 2018) - Shao, L M; Xu, G S; Chen, R; Chen, L; Birkenmeier, G; Duan, Y M; Gao, W; Manz, P; Shi, T H; Wang, H Q; Wang, L; Xu, M; et al.
Abstract: Before L- to H-mode transition small amplitude oscillations (SAOs), different from the widely known intermediate phase (I-phase), at a frequency of a few kilohertz can be observed on EAST. Under sufficient auxiliary heating, SAOs can transit to the H-mode or I-phase. The edge radial electric field ( E r ) located inside the separatrix can be observed to deepen after bursts of SAOs. In SAOs, the turbulence level preceding the negative radial electric field and floating potential perturbation about 90° in phase, consistent with the model of zonal-flows and turbulence interaction, is measured by the Langmuir probe at the bottom of the edge E r well. A physical mechanism for SAOs is developed: at a critical gradient in pressure and E r, turbulence increases at the inboard edge of the E r well. The increased turbulence level enhances the radial particle, energy and momentum transport at the plasma edge and increases the amplitude of the zonal flow at the bottom of the E r well due to the increased Reynolds force. The increase in the zonal flow amplitude acts to mitigate the turbulence on the inboard edge of the E r well, driving a limit-cycle oscillation. The poloidal magnetic perturbations of the oscillations are poloidal in-out/up-down asymmetric and toroidal symmetric in the SAOs.